Co-immunization with spike and nucleocapsid based DNA vaccines for long-term protective immunity against SARS-CoV-2 Omicron - Paolla Beatriz Almeida Pinto; Julia Timis; Kantinan Chuensirikulchai; Qin Hui Li; Hsueh Han Lu; Erin Maule; Michael Nguyen; Rúbens Prince dos Santos Alves; Shailendra Kumar Verma; Fernanda Ana-Sosa-Batiz; Kristen Valentine; Sara Landeras-Bueno; et al. (npj Vaccines)
Abstract The continuing evolution of SARS-CoV-2 variants challenges the durability of existing spike (S)-based COVID-19 vaccines. We hypothesized that vaccines composed of both S and nucleocapsid (N) antigens would increase the durability of protection by strengthening and broadening cellular immunity compared with S-based vaccines. To test this, we examined the immunogenicity and efficacy of wild-type SARS-CoV-2 S- and N-based DNA vaccines administered individually or together to K18-hACE2 mice. S, N, and S + N vaccines all elicited polyfunctional CD4+ and CD8+ T cell responses and provided short-term cross-protection against Beta and Omicron BA.2 variants, but only co-immunization with S + N vaccines provided long-term protection against Omicron BA.2. Depletion of CD4+ and CD8+ T cells reduced the long-term efficacy, demonstrating a crucial role for T cells in the durability of protection. These findings underscore the potential to enhance long-lived protection against SARS-CoV-2 variants by combining S and N antigens in next-generation COVID-19 vaccines.